PENGARUH KUALITAS LAYANAN DAN KEPUASAN TERHADAP WORD OF MOUTH MARKETING - Erwin Sinatra, 10.05.51.0131; Parmono Hadi, Teguh (Students Journal of Economic and Management, 2013)
This research was aiming to test the effect of sevice quality and costumer satisfaction on word of mouth marketing. The research problems refer to companyâs decline of costumer between 2009 until 2012. The research problems are: is service quality has the effect on word of mouth marketing, and is costumer satisfaction has the effect on word of mouth marketing. Researcher used purposive method, that are quota and judgement. The calculation resulted 100 students used as research sample. IBM SPSS 19 was used to process multiple linear regression as analytical tool. The result showed that service quality has positive effect on word of mouth marketing, and costumer satisfaction has positive effect on word of mouth marketing.Key words: service quality, costumer satisfaction, word of mouth marketing.